Os motivos da prática de treinamento de força diferem em relação à idade do praticante - Carla Maria de Liz; Jonathan Nunes Azevedo; Guilherme Torres Vilarino; Fábio Hech Dominski; Alexandro Andrade (Universidade Estadual do Oeste do Paraná, 2015)
The purpose of this study was to relate the practical reasons of strength training at gyms at the age of practitioners. The participants were 328 practitioners of strength training with a mean age of 35 years (± 13.27, min 18 years, max 76 years). We used a characterization questionnaire and Exercise Motivations Inventory-2 (EMI-2). Descriptive and inferential statistics were used for data analysis by adopting significance of 5% (p <0.05). In order of importance, the most cited reasons for practicing strength training were: disease prevention, fitness, fun, stress management, appearance, weight control, affiliation, competition, health rehabilitation and social recognition. The reasons disease prevention, weight control, stress management, membership and health rehabilitation correlated to the age of strength training practitioners, and these have become more important with advancing age. Studies of this nature are critical to understand what leads people of different ages to practice physical exercises in gyms and intervening significantly in the continued practice of these.